A simple and fast formation of biodegradable poly(urethane-urea) hydrogel with high water content and good mechanical property. (2nd September 2016) - Xue, Sasa; Pei, Danfeng; Jiang, Wei; Mu, Youbing; Wan, Xiaobo
Abstract: The synthesis of biodegradable hydrogels with both good mechanical properties and high water content is still a great challenge. In this study, a simple and scalable strategy for the preparation of a biodegradable polyurethane prepolymer composed of isocyanate terminated linear polyethylene glycol (L-PEG) and isocyanate terminated three-armed poly(l -lactic acid) (T-PLLA) is described. When mixed with water, the prepolymer forms a poly(urethane-urea) hydrogel in few minutes. The effect of the molecular weight and the feeding ratio of L-PEG and T-PLLA on the mechanical property of the poly(urethane-urea) hydrogel is discussed. The resulting hydrogel shows good mechanical properties with high tensile strength (up to 108 KPa) and recorded elongation rate (4500%), while maintaining high water content (up to 91% mass ratio). Meanwhile, the maximum water retaining capacity of the hydrogel can be up to 38 times of PU prepolymer (in mass), which is equal to 97.4% water content. Its degradation property is analyzed by the loss of tensile strength and cross section morphology through SEM with time. Such a low cost and biodegradable poly(urethane-urea) hydrogel, which combines fast hydrogel formation, high water content and good mechanical properties, might be used as potential candidates for applications in agrological field, such as sand fixing in desertification control. Graphical abstract: Highlights: Biodegradable hydrogels with both good mechanical properties and high water content were obtained. A simple and scalable strategy for the preparation of a biodegradable PU prepolymer was described. The prepolymer forms a poly(urethane-urea) hydrogel in few minutes when mixed with water. The maximum water retaining capacity of the hydrogel can be up to 38 times of PU prepolymer (in mass).